2023
DOI: 10.1136/bmjopen-2022-068145
|View full text |Cite
|
Sign up to set email alerts
|

Regional practice variation in pelvic organ prolapse surgery in Tuscany, Italy: a retrospective cohort study on administrative health data

Abstract: ObjectivesTo explore determinants of practice variation in both access, and quality and efficiency of surgical care for pelvic organ prolapse (POP).Design and settingA retrospective cohort study employing administrative health data from the Tuscany region, Italy.ParticipantsAll women over 40 years hospitalised for apical/multicompartmental POP reconstructive surgery (excluding anterior/posterior colporrhaphy without concomitant hysterectomy) from January 2017 to December 2019.OutcomesWe first computed treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…In our study, we showed to what extent LC surgery practices depend on the hospital type and size. Few studies have assessed national or regional variations in surgical practice [ 24 , 25 ]. One study, concerning congenital heart surgery, showed the disparity in the outcomes for this surgery according to the hospital and, in particular, the hospital volume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, we showed to what extent LC surgery practices depend on the hospital type and size. Few studies have assessed national or regional variations in surgical practice [ 24 , 25 ]. One study, concerning congenital heart surgery, showed the disparity in the outcomes for this surgery according to the hospital and, in particular, the hospital volume.…”
Section: Discussionmentioning
confidence: 99%
“…The variability was not as marked for hospitals with a high volume [ 24 ]. The other study, from an Italian team, was focused on pelvic organ prolapse surgery and, in particular, the place of the approach (laparotomy or laparoscopy or robotic surgery) [ 25 ]. This very interesting study reported a wide variation in surgical practices between hospitals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations